Comparison of External Carotid Ligation and Pre Operative Embolization of Feeding Vessel for Controlling Per Operative Heamorrhage in Angiofibroma Excision - Zahra Aleem, Bakht Aziz, M. Atiq U Rehman, M. Umair Wahab, Irshad Malik, Kashif Iqbal Malik, Hasnain Haider, Maryam Umar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The prevalence of Angiofibroma of juvenile variety is infrequent tumor of nasopharynx7. It grows aggressively and is locally destructive and extends into the cranium as well. Its symptoms usually involve nasal obstruction with or without nasal bleed. Histopathology shows spindle cells scattered between collagen fibers and vascular tissue. MRI and CT angiogram are the two most important investigations used in its diagnosis. Many methods have been used for its excision since ancient times and many researches have been done to control per operative bleeding as it is a vascular tumor. Aim: This study was performed to compare two methods i.e., 1. Carotid artery ligation per operatively and 2. Embolization of the feeding artery pre operatively in order to assess which method is better in controlling per operative bleeding during its excision. Design: Comparative Setting & duration: Department of Otorhinolaryngology, Jinnah Hospital, Lahore from 01st January 2020 to 31st January 2022. Methodology: A group 20 patients were taken having angiofibroma. 10 patients went for pre operative embolization of the feeding vessel of the angiofibroma after localizing the vessel by having MRA. The other 10 patients had their external carotid artery ligated before excising the angiofibroma. The bleeding which occurred during both procedures was quantified by weighing the gauze pieces soaked per operatively , the blood collected in suction bottle and then comparing the values. Results: The 10 patients who had embolization had far more bleeding during excision as compared to the 10 patients who had their external carotid artery ligated per operatively before excision. Conclusion: Results showed that pre operative embolization is not a better procedure to control per op bleeding as compared to external carotid artery ligation during angiofibroma excision.